The Effect of Dual Diode Laser: (810,980) nm in Acceleration of Orthodontic Tooth Movement:A Case Report - Aya A. Assi*; Rawaa A. Faris; Balsam Saadi Abdulhameed; Sarmad S. Almalki (Iraqi Journal of Laser, 2023)
Patients are very concerned about the lengthy nature of orthodontic treatment. It is necessary to find a non-invasive way to quicken physiologic tooth movement. This study’s objective was to assess the effectiveness of low-intensity laser therapy in shortening the time and discomfort of orthodontic treatment. Experimental work: Using a split-mouth study to compare tooth movement with conventional treatment and laser-accelerated orthodontic tooth movement. A patient presenting with a class II division I malocclusion characterized by the misalignment of the upper and lower teeth as classified by Angle’s molar classification system was indicated to undergo fixed orthodontic appliance orthodontic treatment. The treatment plan involved bilateral extraction of the upper first premolar teeth on both sides and distalization of the anterior segment to close the created space. For an experimental investigation, a patient was chosen at random and given right-side radiation using a dual diode laser (810,980 nm wavelength, 100 mW output power). Results: The tooth movement was measured over a period of 15 weeks; the first three orthodontic activations on the study side included scheduled laser treatment (the first month, laser-assisted treatment on days (0,3,7, and 14), the following two months, on days (0 and 14) from the day of orthodontic activation, and another 3 months of follow-up only); it was observed that orthodontic tooth movement was significantly higher in the study side than in the control side, as measured clinically using a digital vernier. We also noticed a considerable decrease in pain levels following a visual analog test. Conclusion: LLLT might clinically considerably speed orthodontic tooth movement and greatly lessen discomfort using the parameter settings employed in this investigation.